Financial settlements and strategies of discharged patients of St. Anthony College of Roxas City, Inc. (hospital) - Rea Barrera; Nenita Beluso (President University, 2022)
The current crisis posed challenges to management of hospitals providing healthcare services where accounts receivable and payables are crucial to its continued operation. The study investigated the financial settlements and financial settlement strategies of discharged patients of St. Anthony College of Roxas City, Inc. (Hospital). Descriptive-correlational design and simple random sampling were used. The respondents were 237 patients selected at random with outstanding balance upon discharge for the period of November to December 2020. Secondary data from patients’ hospital records were utilized. Statistical tools used to analyse and interpret data were frequency count, percentage, mean, t-test, analysis of variance (ANOVA), and Pearson r. The extent of financial settlements and degree of financial settlement strategies were both high. Research found significant differences in the extent of financial settlements grouped as to medical health insurance, while no significant difference in terms of address, duration of hospitalization, and room accommodation. Further significant differences existed on the degree of financial settlement strategies with regard to address, medical health insurance, and duration of hospitalization whereas room accommodation showed negligible difference. The level of financial settlements was significantly associated with the degree of financial settlement strategies.